2020
DOI: 10.1007/978-3-030-58904-2_8
|View full text |Cite
|
Sign up to set email alerts
|

Physiology and Molecular Biology of Trace Element Hyperaccumulation

Abstract: Metals (trace elements) are essential for plants but become toxic at high concentration. Remarkably, about 700 species worldwide are able to accumulate large quantities of metals in their leaves and are therefore called metal hyperaccumulators. In the context of sustainable development, there is renewed interest in understanding the mechanisms of metal hyperaccumulation that may become instrumental for improved metal phytoextraction from contaminated soils and for making metals available at lower environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 271 publications
(371 reference statements)
0
18
0
Order By: Relevance
“…The first stage is the uptake and transport of a metal by the roots. The primary role in this process is played by members of the ZIP family (the zinc-regulated transporter/iron-regulated transporter-like proteins), whose expression is high in the roots and/or shoots of hyperaccumulating plants [ 45 , 46 , 67 ]. ZIP19 and ZIP23 transporters are mainly responsible for the uptake of zinc by the roots of A. halleri and N. caerulescens [ 46 ].…”
Section: Arabidopsis Arenosa and Heavy Metalsmentioning
confidence: 99%
See 3 more Smart Citations
“…The first stage is the uptake and transport of a metal by the roots. The primary role in this process is played by members of the ZIP family (the zinc-regulated transporter/iron-regulated transporter-like proteins), whose expression is high in the roots and/or shoots of hyperaccumulating plants [ 45 , 46 , 67 ]. ZIP19 and ZIP23 transporters are mainly responsible for the uptake of zinc by the roots of A. halleri and N. caerulescens [ 46 ].…”
Section: Arabidopsis Arenosa and Heavy Metalsmentioning
confidence: 99%
“…ZIP19 and ZIP23 transporters are mainly responsible for the uptake of zinc by the roots of A. halleri and N. caerulescens [ 46 ]. In non-hyperaccumulator species, the expression of several ZIP genes is low and increases during Zn deficiency [ 46 , 67 ]. In addition, it was found that Cd treatment induces the higher expression of genes related to Cd uptake and transport in roots ( IRT1 , ZIF1 ) and shoot ( ZIF1 and YSL3 ), as well as Cd vacuolar sequestration ( HMA3 ) [ 68 ].…”
Section: Arabidopsis Arenosa and Heavy Metalsmentioning
confidence: 99%
See 2 more Smart Citations
“…The physiological mechanisms underlying hyperaccumulation have been intensively studied and current knowledge is summarized in recent reviews representing many perspectives, including genetic, molecular, and evolutionary biology [13][14][15][16][17][18][19][20]. In very broad terms, hyperaccumulation involves the two suites of processes that can be termed metal accumulation and metal tolerance.…”
Section: Introductionmentioning
confidence: 99%